Diethyl Ether Production Process with Various Catalyst Type - Widayat Widayat; Achmad Roesyadi; Muhammad Rachimoellah (International Journal of Science and Engineering, 2013)
Several H-zeolite and HZSM-5 catalysts was preparated and their characters have also been investigated. H-zeolit Catalyst was preparated from Natural Zeolite that obtained from Malang District and Gunung Kidul District. Diethyl ether was produced by Ethanol with concentration of 95%. This research use fixed bed reactor that 1 gram of catalyst as bed catalyst, atmospheric pressure and temperature 140oC as the operating condition. Ethanol vapor from vaporization tank was driven by 200 ml/min Nitrogen stream. The responds in this research is liquid product concentration; diethyl ether, ethanol, methanol and water concentration. The results showed that the largest ethanol conversion was produced by the use of 56.44% HZSM-5 and the largest yield of diethyl ether diethyl was produced by the use of alumina and H-zeolite catalyst. The larger ratio between natural zeolite with HCl solvent will produce the larger surface area of catalyst and ethanol conversion. The largest ethanol conversion was produced at reactan ratio 1:20. [Keywords:  catalyst; ethanol conversion; dehydration process; yield of diethyl ether; natural zeolite].